Sistem Informasi Optimasi Produksi dengan Metode Simplex Guna Penentuan Laba Maksimum - Ferrentino Sutjiadi; Siti Aminah (LPPM STIKI MALANG, 2020)
PT. Poci Kreasi Mandiri is one of the well-known companies in Indonesia that is engaged in selling tea. This company collaborates with franchisees (franchise recipients) in running their business. The recording carried out by the franchisee of this company is still manual, starting from recording stock items, recording sales, recording profits, managing sales planning, to determining profit income is still carried out manually, and recorded in a book. Manual recording from the planning process to profit achievement has the potential for human error, which is an error or some mistakes in the process of recording and calculating profits. This can prevent franchisee from reaching maximum profit. This franchisee company still does not have the right system to carry out the production administration process and does not yet have the right method to optimize production and determine maximum profit. In accordance with the problems faced by the franchisee of this company, researcher built a system to make it easier to assist the administrative recording process and optimize production. The production optimization process is carried out using the linear programming method with the simplex method approach. The optimization result of using the simplex method on the system is how many products must be produced to achieve maximum gross profit. Franchisee can achieve a total profit of Rp43,299,700.00 through the implementation of production that was carried out in January, 2020. Meanwhile, the production optimization system shows that franchisee can still reach a total profit of Rp66,300,050.00.